#### Answer

(a) $3$
(b) $4$
(c) $1$
(d) $-2$

#### Work Step by Step

(a) $(g\circ f)(1)=g(f(1))=g(-1)=3$
(b) $(g\circ f)(5)=g(f(5))=g(1)=4$
(c) $(f\circ g)(0)=f(g(0))=f(5)=1$
(d) $(f\circ g)(2)=f(g(2))=f(2)=-2$

Published by
Pearson

ISBN 10:
0-32193-104-1

ISBN 13:
978-0-32193-104-7

(a) $3$
(b) $4$
(c) $1$
(d) $-2$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.